Improved lateral penumbra for proton ocular treatments on a general-purpose spot scanning beamline. (March 2023) - Saini, Jatinder; Maes, Dominic; Regmi, Rajesh; Fung, Angela; Bloch, Charles; Schwarz, Marco; Stacey, Andrew; Chen, Jonathan; Rengan, Ramesh; Halasz, Lia
Highlights: Our solution converts a commercial IBA high energy scanning beamline to allow for ocular proton therapy. Abstract: Purpose: An ocular applicator that fits a commercial proton snout with an upstream range shifter to allow for treatments with sharp lateral penumbra is described. Materials and Methods: The validation of the ocular applicator consisted of a comparison of range, depth doses (Bragg peaks and spread out Bragg peaks), point doses, and 2-D lateral profiles. Measurements were made for three field sizes, 1.5, 2, and 3 cm, resulting in 15 beams. Distal and lateral penumbras were simulated in the treatment planning system for seven range-modulation combinations for beams typical of ocular treatments and a field size of 1.5 cm, and penumbra values were compared to published literature. Results: All the range errors were within 0.5 mm. The maximum averaged local dose differences for Bragg peaks and SOBPs were 2.6% and 1.1%, respectively. All the 30 measured point doses were within +/-3% of the calculated. The measured lateral profiles, analyzed through gamma index analysis and compared to the simulated, had pass rates greater than 96% for all the planes. The lateral penumbra increased linearly with depth, from 1.4 mm at 1 cm depth to 2.5 mm at 4 cm depth. The distal penumbra ranged from 3.6 to 4.4 mm and increased linearly with the range. The treatment time for a single 10 Gy (RBE) fractional dose ranged from 30 to 120 s, depending on the shape and size of the target. Conclusions: The ocular applicator's modified design allows lateral penumbra similar to dedicated ocular beamlines while enabling planners to use modern treatment tools such as Monte Carlo and full CT-based planning with increased flexibility in beam placement.